Pengabdian kepada Masyarakat Melalui Peningkatan Pemahaman Pembayaran Digital Quick Response Code Indonesian Standard bagi Pelaku Umkm Desa Lereng - Suyanto, Suyanto; Mulyadri, Rizki; Fauzan, Akmal; Resiartha, Ayu Yudits Reivasya; Ananta, Cornelia; Sianturi, Kefin Adrian; Ramadani, Nadya; Gardewa, Randy; Ardiansyah, Rizky; Pujangga, Sri; Opiani, Yeni; Istiqomah, Zhulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
QRIS (Quick Response Code Indonesian Standard) is a QR code standardization from Bank Indonesia used for digital payments in Indonesia. QRIS unifies various digital payment methods—so with just one QR code, all digital wallet applications or mobile banking can be used to pay. In the economic aspect, the problem is that most MSMEs in the Lereng villages currently still use cash payments. The people of the Lereng Village are not yet familiar with digital payment systems such as QRIS (Quick Response Code Indonesian Standard). Answering this problem, this community service program aims to increase public understanding, especially MSMEs (Mikro, Small, and Medium Enterprises), of digital payment systems such as QRIS. With the socialization and education about QRIS, the community is expected to be able to utilize digital technology to support the efficiency and progress of their businesses. The implementation method applied includes socialization by explaining directly and implementing it for MSME business actors. The results of these activities, the community gains knowledge and understanding of digital payment systems as an alternative for fast, safe, and efficient transactions. Thus, the introduction of QRIS can encourage business actors to start adapting to technological developments, thereby increasing competitiveness and expanding the marketing reach of their businesses.